HEDONIC VALUATION OF MARGINAL WILLINGNESS TO PAY FOR AIR QUALITY IMPROVEMENT - Saptutyningsih, Endah; Basuki, Agus Tri (Economic Journal of Emerging Markets, 2014)
Abstract This study aims to identify the highest air pollution areas and to estimate household marginal willingness to pay for air quality improvement. The result of Kriging technique indicates that six sub districts in Yogyakarta City and one sub district in Gunungkidul have highest concentration of particle pollution (PM10). The result of hedonic price method conclude that by adopting a two-stage estimation procedure an 1% increase in the level of PM10 reduced property prices in the study area by 0.32%. Marginal implicit price for reducing PM10 is Rp 957,900.00. The households are willing to pay an additional amount of 1.34 percent for a reduction in PM10 by 1%. Keywords: Air pollution, marginal willingness to pay, hedonic price, implicit price JEL classification numbers: D12, Q53 Abstrak Penelitian ini bertujuan mengidentifikasi daerah polusi udara tertinggi dan untuk memperkirakan kesediaan marginal rumah tangga untuk membayar untuk perbaikan kualitas udara. Dengan menggunakan teknik Kriging, hasil penelitian menunjukkan bahwa enam kecamatan di Kota Yogyakarta dan satu kecamatan di Gunungkidul memiliki konsentrasi tertinggi partikel polusi (PM10). Sementara itu, dengan metode harga hedonik yang mengadopsi prosedur dua tahap, paper ini menyimpulkan bahwa setiap peningkatan PM10 sebesar 1% akan menurunkan harga properti di daerah penelitian sebesar 0.32 persen. Harga implisit marjinal untuk mengurangi PM10 adalah Rp 957,900. Rumah tangga bersedia membayar tambahan 1,34 persen untuk pengurangan PM10 sebesar 1%. Kata kunci: Polusi udara, keinginan membayar marjinal, harga hedonik, SIG, harga implisit JEL classification numbers: D12, Q53